Uji Aktivitas Antioksidan Gummy Candy Ekstrak Daun Sirih Cina (Peperomia pellucida L. Kunth) dengan Metode DPPH - Ni Putu Putri Cahya Anggreni; Ni Putu Refina Dharma Yanti; Kadek Ayu Puspa Pratiwi; Ni Nyoman Wahyu Udayani (Indonesian Journal of Pharmaceutical Education, 2023)
The body's defense that functions to neutralize free radicals is antioxidants. The Peperomia pellucida is a medicinal plant that has secondary metabolite compounds such as alkaloids, flavonoids, saponins, tannins and steroids. Antioxidants in Chinese betel plants are associated with the prevention and treatment of several diseases. The aim of this research was to determine the antioxidant activity contained in Peperomia pellucida and Peperomia pellucida gummy candy preparations. This research uses the main ingredient of peperomia pellucida obtained from the Jembrana district, Bali province. The total weight of the extract obtained was 30 grams. Then the materials used are peperomia pellucida extract gummy candy, DPPH powder, 96% ethanol, chloroform, ammonia, H2SO4, Dragendorf reagent, concentrated HCL, magnesium powder, CH3COOH, iron (III) chloride, distilled water. This research uses the DPPH method in antioxidant testing and phytochemical screening testing in testing peperomia pellucida extract. The results of the phytochemical screening test for peperomia pellucida extract showed positive results in the alkaloid, flavonoid, steroid, saponin and tannin tests. In the results of the antioxidant activity test using the DPPH method, the antioxidant activity results of Chinese betel extract showed an IC50 value of 564,062 ppm. Gummy candy peperomia pellucida extract 100mg/kgBB showed an IC50 value of 904,342 ppm. In gummy candy, peperomia pellucida extract 200mg/kgBB showed an IC50 value of 381.205 ppm. And gummy candy peperomia pellucida extract 400mg/kgBB showed an IC50 value of 347,227 ppm. Based on the research results obtained, it can be said that the IC50 value is very weak. This can be seen from the IC50 value 200 ppm. Based on the results of research, from Chinese betel extract, gummy candy Chinese betel extract doses of 100mg/kgBB, 200mg/kgBB, and 400mg/kgBB which contain the best antioxidants, which are found in gummy candy formula 200 mg/kgBB with results of 347,227 ppm.